GTN - Information System Supporting the Dispatcher and Remote Tracks Control - Krsak, Emil; Bachraty, Hynek; Polach, Vlastimil (Communications - Scientific Letters of the University of Zilina, 2010)
When constructing new corridor tracks, but also when reconstructing the existing ones of all categories, new significant improvements and innovations occur in the contruction area. Consequently, the same phenomenon occurs in the newly installed securing, interlocking and signalling equipment, and generally enabling also remote track control. The traffic information and controlling system (hereinafter the GTN) being developed by the Software Technologies Department of the University of Zilina in cooperation with the AZD Praha Company, represents a graphical and technological extention of the electronic signalling equipment. It contains a compact data, technology and software model of railway operation, enabling to receive information from the securing, interlocking and signalling equipment, as well as from other information and controlling railway systems, about trains' movement. It also enables to save, display and document the traffic progression, trains movement and technological operations on them. Last but not least, it provides opportunity to display the anticipated prognosis of the traffic situation, and transmit information about trains movement towards external IS, e. g. the passenger information systems at the stations etc. Currently, the GTN system has been implemented and used in several versions on the Czech and Slovak Railways tracks. Hereby we would like to introduce its latest solution based on distributed architecture using a database system.
Keywords: no keywords